Assessment of genetic divergence and principal component analysis in oil palm (Elaeis guineensis Jacq.): ASSESSMENT OF GENETIC DIVERGENCE AND PRINCIPAL COMPONENT ANALYSIS IN OIL PALM - ANITHA PEDAPATI; R K MATHUR; G RAVICHANDRAN; B KALYANA BABU; H P BHAGYA (Journal of Oilseeds Research, 2018)
Twenty-nine oil palm DxD crosses derived from 37 dura parents were evaluated to identify high yielding and dwarf palms. Yield performance of progenies of 29 oil palm DxD crosses varied significantly and it ranged from 102.53 to 191.37 kg/palm/year with an experimental mean of 145.95 kg/palm/year. The other yield related traits like sex ratio and bunch number also significantly varied. Palmheight increment after five years of planting ranged from 20.40 to 31.44 cmwith experimental mean of 25.93 cm. Based on cluster analysis, all 29 DxD crosses with important traits grouped into five distinct clusters. From the present study, eight genotypes (DD7, DD8, DD11, DD12, DD17, DD18, DD21, and DD22) were identified to be high yielding and with slow vertical growth habit. Among the cluster IV DxD crosses, DD7 and DD8 had a common parent 257 CD; DD17 and DD18 had a common parent 232 CD. The preferred genotypes in the present diversity studies could be utilized as desirable parent in hybridization programme which led to the improvement of dura oil palm in high yield and slow vegetative growth.